Prevalence of Depression in Physical Therapists Versus Nurses in Karachi Pakistan: Depression in Physical Therapists Versus Nurses - Ali, Sabina Anwer; Jamil, Komal; Lata, Prem; Kumar, Vinesh; Arzoo, Obaida; Hassan, Muhammad Faizan; Abro, Sara Aamir; Ilyas, Lubna (Pakistan BioMedical Journal, 2024)
Depression is one of the major mental disorders that affect the population of Pakistan with a prevalence rate of 40.6% in females and 32% in males. It affects the population of all ages. It also affects the mental health of Healthcare workers which impacts the quality of life of patients whom they care for in the working environment. Objective: To determine the prevalence and severity of depression among the physical therapists and nurses of Karachi. Methods: It was a cross-sectional study, conducted between Dec 2023 to May 2024 with a sample size of 661 calculated through Raosoftware. The Non-probability convenient sampling technique was used for sample selection. Data were collected through the Beck inventory questionnaire. The analysis of data were done through SPSS version 23.0. Results: The sample size of 661 research participants from which 310 were physical therapists and 351 were nurses recruited from 7 districts of Karachi. The level of depression was measured throgh Beck inventory questionnaire. The results found that the prevalence of depression is 64.67% in nurses and 36.12% in physical therapist. In addition, 63.83% physical therapists were more satisfied with their lifes while the level of satisfaction of nurses was 33.33%. Conclusions: It is concluded that depression is present in both professions but nurses are more depressed as compared to physical therapists.